The Capabilities Driving Participation in Global Value Chains - Pathikonda, Vilas; Farole, Thomas (World Bank, Washington, DC, 2016)
Global value chains have altered the nature of global trade and offer significant opportunities for developing countries to expand exports, access technology, and raise productivity. Policy makers rightly seek to understand what it takes to participate in global value chains. In practice, this means understanding what it takes to attract lead firms and upgrade to higher value-added activities. Recent literature has pointed to a range of underlying characteristics that may drive participation in global value chains. Using a modified factor-content methodology, this paper shows that proximity to markets, efficient logistics, and strength of institutions are among the most important capabilities. However, the paper also shows that each sector has a unique mix of capability requirements. Fixed structural characteristics limit the range of sectoral possibilities for a given country, but, by reducing policy-related gaps, a country may be able to increase its competitiveness for participating in global value chains. The paper applies the methodology to Southern African Customs Union countries, and demonstrates that, by filling gaps in underlying capabilities, these countries could increase participation in certain global value chain sectors.